Using Community-Partnered Participatory Research to Value the ?Community Lens? and Promote Equity in Community?Academic Partnerships (Mary Ann Liebert, 2023)
Background: Community input is crucial for identifying characteristics necessary for equitable, sustainable community?academic partnerships (CAPs). A November 2021 conference, honoring the late Dr. Loretta Jones and the Community-Partnered Participatory Research (CPPR) model, was held to gather input for designing a learning institute for community members as co-equal partners with academics in research, program, and policy initiatives. This created an opportunity to explore attendees' perspectives on challenges and opportunities related to CAPs with special focus on promoting equity. Methods: Institutional Review Board approval was obtained. Five break-out discussion group sessions were conducted in November 2021 co-facilitated by both an academic and a community leader. After consent, discussions were recorded and transcribed. An iterative procedure for collaborative-group-thematic-analysis was developed. The six-phase process included rigorous coding, discussion, comparison of data with data, and development and refinement of themes and subthemes. Results: A total of 38 racial-ethnically diverse participants volunteered from the total conference audience of 62 community and academic partners from various sectors including community-based organizations, health care, social services, academia, or policy within Los Angeles County. Analysis led to development of three themes: Being cautious with the extractive tendency of academia and the need for anti-racism within CAPs; Leveraging community power to resist the top-down lens of academia; and bridging two worlds through an equitably structured table. Discussion: Participants described optimism about the future uses of CPPR to enhance CAPs, and the need to address barriers to equitable partnerships owing to unequal social contexts and entrenched power dynamics. Implications include addressing racism, evaluating financial equity in partnerships to promote accountability, and mentoring community leaders to promote equity. Conclusion: Use of a ?community lens? for developing sustainable, equitable CAPs is crucial to promote accountability and to responsibly implement authentic CPPR.